PENYERBUKAN PADA PINANG YAKI (ARECA VESTIARIA) DI KEBUN RAYA BOGOR - N. UTAMI; SIH KAHONO (Research Center for Biology-Indonesian Institute of Sciences, 1989)
N. UTAMI & SIH KAHONO. 1988. Pollination on the pinang yaki (Areca vestiaria Giseke) in the Bogor Botanical Gardens. Berita Biologi 3(9): 470 -472.Morphology,flowering biology of the pinang yaki was observed at the Bogor Botanical Gardens.This plant i&imonocious and self pollinated. However,insect visitors appear to play an importantrole of fruit setting.It was showed that the number of fruits setting in isolated inflorescence were smaller than in unisolated inflorescence.During anthesis,the inflorescence were visited by ten species of insects,and Trigona iridipennis was suspected as the palm pollinator.